2021
DOI: 10.21776/ub.jam.2021.019.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Utilitarian Shopping Value and Hedonic Shopping Value to Improve Customer Satisfaction and Repurchase Intention on E-Commerce Business

Abstract: This study aims to examine and analyze the relationships between motivation shopping value, repurchase intention, and customer satisfaction on Lazada Indonesia’s ecommerce consumers in Malang City. The population of this research is Lazada Indonesia consumers who are of productive age (19-34 years old) in Malang City and the number of samples obtained following the research criteria is 100 correspondents. Sample selection is done by the non-probability sampling technique with the purposive sampling method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
2
4
0
1
Order By: Relevance
“…Hedonic values are indeed more subjective and personal because they are directly related to the emotional desires of each individual when shopping (Rintamäki et al, 2006). This result is also the same as several previous studies, which indicated a positive relationship between hedonic value and customer satisfaction (Andriani et al, 2021), reducing negative feelings and relieving stress (Evelina et al, 2020). Hedonic value is also obtained when consumers are satisfied when making transactions through websites or applications.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Hedonic values are indeed more subjective and personal because they are directly related to the emotional desires of each individual when shopping (Rintamäki et al, 2006). This result is also the same as several previous studies, which indicated a positive relationship between hedonic value and customer satisfaction (Andriani et al, 2021), reducing negative feelings and relieving stress (Evelina et al, 2020). Hedonic value is also obtained when consumers are satisfied when making transactions through websites or applications.…”
Section: Resultssupporting
confidence: 87%
“…Some studies discussed these two topics separately (Chung et al, 2016;Mustikasari & Astuti, 2021). Shopping value was discussed in the context of online retail shops or e-commerce (Andriani et al, 2021;Evelina et al, 2020). E-service quality topics for online grocery are limited (Chung et al, 2016;Muhammad et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Nova Andriani et al (2021) analyzed that hedonic and utilitarian shopping values affect satisfaction and repeat purchases in general. However, this study recommends that it be carried out more specifically and with a larger sample coverage of more specific objects.…”
Section: Research Conducted Bymentioning
confidence: 99%
“…Based on this, this research is intended to develop from previous studies, especially developing research by Nova Andriani et al (2021). This study will focus on hedonic and utilitarian shopping values to increase satisfaction and repurchase intentions on online food and beverage purchases in Indonesia.…”
Section: Research Conducted Bymentioning
confidence: 99%
“…Do đó, điều rất quan trọng là xác định các yếu tố ảnh hưởng đến ý định mua lại trực tuyến của khách hàng. Hiện nay, các nghiên cứu liên quan đến ý định mua lại trực tuyến đã và đang được sự quan tâm của các nhà nghiên cứu nước ngoài (Chẳng hạn như Jayathilaka, 2020;Yolanda & Putri, 2021;Andriani et al, 2021). Tuy nhiên, bối cảnh nghiên cứu của các nghiên cứu ở nước ngoài có thể khác với bối cảnh nghiên cứu tại Việt Nam, do đó kết quả nghiên cứu có thể có sự khác biệt.…”
Section: Giới Thiệuunclassified